Trends and Disparities in Quality of Life Among Older Adults From 1998 to 2018 in China: A National Observational Study - Liu, Jue; Wang, Jun (Frontiers in Medicine, 2022)
Objective To investigate 20-year trends and disparities in quality of life among older adults in China from 1998 to 2018. Methods Our study was based on eight representative nationwide health surveys among older adults conducted in China from 1998 to 2018. Quality of life data were obtained from 91993 individuals aged 65 years or above. All surveys included identical indicators of self-reported quality of life, demographic factors, socioeconomic status, lifestyle habits, and health status. The trends in the standardized prevalence of poor quality of life from 1998 to 2018 were examined by locally weighted scatterplot smoothing regression (LOWESS) analysis. We assessed the prevalence of poor quality of life and its related factors by logistic regression models, after adjusted for potential confounders. Results The prevalence of poor quality of life was 38.2% (95% CI: 37.9%-38.5%). The trends of poor quality of life showed an inverted “U” shape, that the prevalence increased from 27.8% in 1998 to 43.6% in 2008, and then decreased from 39.2% in 2011 to 32.1% in 2018. Disparities in the prevalence of poor quality of life were exacerbating among participants with low or moderate household income per capita and participants with high household income per capita from 1998 to 2018. After controlling potential confounders, living in rural areas, aged below 80 years, unmarried, living alone, low household income, current smoker, poor dietary diversity, never participating in organized social activities, with chronic diseases, functional disability, poor self-reported health, unhealthy psychological status were risk factors related with poor quality of life in the multivariate model (all p<0.05). Conclusion During the past two decades, poor quality of life in Chinese older adults showed an inverted “U” trend from 1998 to 2018 that the prevalence of poor quality of life peaked at 2008 and declined since China’s deepening health system reform in 2009. However, disparities in the poor quality of life were exacerbating among participants with different socioeconomic status. Strengthening health system is of great importance on improving quality of life. More efforts are needed to reduce the disparities in quality of life among population in different socioeconomic level.